1991
DOI: 10.1016/0042-6822(91)90144-z
|View full text |Cite
|
Sign up to set email alerts
|

cis acting RNA sequences control the gag-pol translation readthrough in murine leukemia virus

Abstract: The pol gene of the Moloney murine leukemia virus (M-MuLV) is expressed as a Gag-Pol fusion protein through an in-frame suppression of the UAG termination codon located between the two genes. The role of nucleotide context in suppression was investigated, in a rabbit reticulocyte lysate translation system, using site-directed mutagenesis. The results indicate that the translational readthrough is mediated by at least 50 bases long RNA sequence located 3' to the gag UAG termination codon. Within this sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
5
26
1
Order By: Relevance
“…On the basis of these observations, Jones et al ( 1989) suggested that a region of secondary structure near the UAG codon must be preserved; however, their study did not test the effect of destabilizing mutations upstream of the UAG codon (e.g., A2223 to C alone) nor did they measure suppression directly. In a related series of experiments carried out in uitro, Honigman et al (1991) introduced destabilizing mutations into residues in the stem of the putative stem-loop structure ( Fig. 3 ) a t positions 5' (nt 2222-2226, GACCC to AAUAU) and 3' (nt 2246-2250, GGGUC to UCAUG) of the UAG codon.…”
Section: Possible Suppression Signals In Mammalian Type C Retroviral mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these observations, Jones et al ( 1989) suggested that a region of secondary structure near the UAG codon must be preserved; however, their study did not test the effect of destabilizing mutations upstream of the UAG codon (e.g., A2223 to C alone) nor did they measure suppression directly. In a related series of experiments carried out in uitro, Honigman et al (1991) introduced destabilizing mutations into residues in the stem of the putative stem-loop structure ( Fig. 3 ) a t positions 5' (nt 2222-2226, GACCC to AAUAU) and 3' (nt 2246-2250, GGGUC to UCAUG) of the UAG codon.…”
Section: Possible Suppression Signals In Mammalian Type C Retroviral mentioning
confidence: 99%
“…The upstream mutation had no effect on suppression in the in uitro system; in contrast, the downstream mutation prevented readthrough. These results led Honigman et al (1991) to conclude that a secondary structure involving the UAG codon and nearby nucleotides at the MuLV gug-pol junction is unlikely to be important in suppression and in addition emphasized the role of the downstream sequences. It is interesting that stem-loop structures similar to the one shown in Fig.…”
Section: Possible Suppression Signals In Mammalian Type C Retroviral mentioning
confidence: 99%
“…MoMuLV PR(Ϫ) contains a D32L substitution (nucleotides GAT to CTT) at the active site of PR preventing protease activity. The readthrough event that produces MoMuLV Gag-Pol is dependant on a bipartite signal consisting of a purine-rich region immediately downstream from the Gag TAG codon (15,25), followed by a RNA pseudoknot structure (25). MoMuLV Gag UAA contains an additional termination codon at amino acid 18 of the PR gene (nucleotides ATA to TAA) downstream of the readthrough RNA stem-loop structure, which prevents translation of full-length PR, RT, and IN.…”
Section: Methodsmentioning
confidence: 99%
“…In murine leukaemia virus (MLV), a 63-nucleotide read-through signal folds as a pseudoknotted 79 structure (MLV-PK) that can independently direct recoding of stop codons 5,6,10 , even in heterologous RNA (see Supplementary Text and Supplementary Fig. 1a).…”
mentioning
confidence: 99%